Correlation between enlarged perivascular space and brain white matter hyperintensities in patients with recent small subcortical infarct - Xiuli Jian; Fubiao Xu; Mi Yang; Min Zhang; Wenwei Yun (Brain and Behavior, 2023)
Abstract Background This study aimed to investigate the correlation between enlarged perivascular space (EPVS) and white matter hyperintensities (WMH) at different locations in patients with recent small subcortical infarct (RSSI). Methods Data were collected from patients with RSSI who were hospitalized at Changzhou Second People's Hospital between October 2020 and December 2021. All patients underwent cranial magnetic resonance imaging, and the grades of EPVS and WMH were assessed, including basal ganglia EPVS (BG‐EPVS), centrum semiovale EPVS (CSO‐EPVS), deep WMH (DWMH), and periventricular WMH (PWMH). The volumes of EPVS and WMH at different locations were quantified using 3D Slicer software. Patients were grouped according to the severity of BG‐EPVS and CSO‐EPVS. Univariate and multivariate analyses were used to analyze the relationship between EPVS and WMH. Results A total of 215 patients with RSSI were included in the analysis. Patients with moderate‐to‐severe BG‐EPVS had higher DWMH and PWMH severity than those with mild BG‐EPVS, both in terms of volume and grade. There was no significant difference in WMH severity between patients with mild CSO‐EPVS and those with moderate‐to‐severe CSO‐EPVS. Multivariate analysis indicated that after adjustments were made for confounding factors, DWMH volume (β = 0.311; 95% CI, 0.089–0.400; p = .002) and PWMH volume (β = 0.296; 95% CI, 0.083–0.424; p = .004) were independently associated with BG‐EPVS. Pearson correlation showed that PWMH volume (r = .589; p < .001) and DWMH volume (r = .596; p < .001) were positively related to BG‐EPVS volume. Conclusion DWMH and PWMH are closely related to BG‐EPVS in patients with RSSI.